Pengembangan Media (Bingkap) dalam Pembelajaran Menulis Teks Pantun dengan Menggunakan Model Project Based Learning - Angga Angga; Lutfi Syauki Faznur (Politeknik Kampar, 2025)
This research was conducted at Dharma Karya UT South Tangerang Junior High School in class VII which amounted to 26 people. This research was motivated by the lack of learning media. The learning media used by teachers only use printed books, the internet and powerpoint and the learning model used by teachers is only cooperative learning, so that the impact on students is easily bored and bored in participating in the learning process. This study aims to produce Pop-Up book media (Bingkap) and make rhyming text using the Project Based Learning (PjBL) model in class VII SMP Dharma Karya UT South Tangerang which meets valid and practical criteria. This type of research is Richey & Klein research. The development model uses 3 stages. The stages carried out are planning, production, and evaluation. In the validation process, Bingkap media was validated by 2 validators, namely media expert validators and material expert validators. In the development process, teachers fill out a questionnaire sheet to be able to see the developed Bingkap media. Based on this research, the results of media expert validation obtained a percentage of 90% with the criteria “Strongly Agree”. The results of material expert validation 88.33% with the criteria “Strongly Agree”. From the results of the response questionnaire by the seventh grade teacher obtained a percentage of 100% with the criteria “Strongly Agree”. This shows that the Pop-Up book media (Bingkap) using the Project Based Learning (PjBL) model in learning to write Indonesian rhyming text in class VII SMP Dharma Karya UT South Tangerang is declared Strongly Agreed or Very Valid in the learning process.